Synthesis, Characterization, and Gas Transport Properties of New Copoly(Ether-Amide)S Containing Benzophenone Aromatic Isophthalic Segment - Sanchez-Poblete, J (Sociedad Chilena de Quimica, 2016)
Three new copoly(ether-amide)s based on polyether segments of different molecular weight (average molecular weight 400, 900 and 2000 g/mol) and polyamide segments obtained from 4,4 -diamine benzophenone (DBF) and isophthalic acid (ISO) are reported. The resulting new copoly(ether-amide)s have inherent viscosities ranging of 0.32 to 0.35 dL/g at concentration of 0.5 g/dL, and form dense membranes by solvent casting method. The gas transport properties of the new copoly(ether-amide) membranes for pure gases (He, CO2, O2, CH4, and N2) are studied at different pressures (2.0, 5.0, 7.5, and 10.0 atm) and at different temperatures (35-75 °C). The soft segment of polyether allows an increase in gas permeability coefficients, mainly CO2, in comparison with the values reported for DBFISO aromatic polyamide. However, an increase in polyether segment length decreases the overall permeability coefficients, because the polyether shows a strong tendency to crystallize.